Konstruksi Teologi Revolusioner Hassan Hanafi - Lukman Hakim (Substantia: Jurnal Ilmu-Ilmu Ushuluddin, 2010)
Historically, Islamic theology ever became a soul of revolution that alleviated the Islamic empires to the most glorious civilization on the world. By the rationalized theological system, Islam succeeded in enlightening human thoughts. Ironically, the glory could not be maintained by past Muslim which caused the civilization went under and could not be able to compete with other raising civilizations. Theologically, the collapse of muslim civilization was caused by Muslim inability to cultivate the revolution spirit that lies within Islamic theological doctrines. The presence of Hassan Hanafi becomes a fresh air that blows the development of Islamic civilization by offering the concept of revolutionary theology. Hassan Hanafi’s construction of revolutionary theology focuses on four big steps covering (1) revitalization of the enrichment of classical Islam (Ihya al-turats al qidim), (2) responding the western challenges (tahadda al hadarah al gha